Modification to the Transparency Policy. (Policy Papers; Policy Paper, 2022)
The new Debt Sustainability Framework for Market Access Countries (MAC SRDSF) contemplates certain output that would be shared with the Board but that would need to be deleted from Country Documents before publication. A targeted modification to the Transparency Policy-proposed in this paper-is required for such deletions to be applied across market access Country Documents rather than on a case-by-case basis. The MAC SRDSF output to be deleted before publication consists on: (i) the near-term risk assessment; (ii) when debt is assessed to be sustainable, the qualification "with high probability" or "but not with high probability", unless such qualification is required for use of Fund resources; and (iii) the mechanical signal on debt sustainability.